ANALISIS PENERAPAN ASAS RETROAKTIF DALAM PUTUSAN PENGADILAN NEGERI DENPASAR NOMOR 167/PID.B/2003/PN.DPS TERKAIT KASUS TINDAK PIDANA TERORISME BOM BALI 1 - Dhika Paskah Adi Putri; Ismaya Salindri; Yosua Revie Nouke Satria (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2013)
AbstractThe purpose of this study is to ascertain the application of the retroactive principle on the terrorism case. This study is descriptive or applied in legal research and the writers use normative legal research. Based on the research that Indonesian law had legislation which criminalize of terrorism, compiled after the the Bali Bombing I. In the formulation of terrorism statute applicable the retroactive principle for terrorism cases that happened previously included the Bali Bombing I which ultimately give punishment to the perpetrators of the bombing and also give a sense of justice to the victims as well as the legal certainty for all.Keywords: retroactive principle, terrorism, terrorism statute.